Strategy Interest of Dual SystemVocational Education Training and Development to Prepare Competence-Based Human Resources - Darsono, Darsono; Kartono, Drajat Tri; Anantanyu, Sapja (Advances in Social Sciences Research Journal, 2019)
Preparatory programs for the textile and textile product industry workforce are carried out through vocational education and training as well as competency certification, especially in areas becoming centers of growth and distribution of the textile and textile products industry. This research focuses primarily on the influence of strategic interests in the training and development of textile and garment industry companies in the development of community college programs; the influence of human resource competence on the development of higher education programs; and the influence of the role of the government in the development of higher education programs. The sampling technique used in this study was Saturated Sampling where the number of research samples was 320 respondents. Data processing and analysis techniques in this study use Partial Least Square (PLS) approach using PLS-SEM 3.0 software. The findings in this study indicate that First, the importance of strategic training and company development in the textile and garment industry has a positive and significant influence on the development of higher education programs. Second, human resource competence has a positive and significant impact on the development of community college programs. Third, the role of the government in preparing human resources has a positive and significant influence on the development of higher education programs.